CO2 adsorption using 3-triethoxysilylpropylamine (aptes)-modified commercial rice husk activated carbon - Muhammad Zubair, Abdul Wahab Saaroni; Hamidah, Abdullah; Emyra Ezzaty, Masiren; Khan, Maksudur R. (Universiti Malaysia Pahang, 2018)
Carbon dioxide (CO2) is one of the greenhouse gases that causes global warming. Therefore, there is a need for CO2 capture technologies in order to reduce the CO2 emissions to the atmosphere. In this study, commercial rice husk activated carbon was impregnated with 3-triethoxysilylpropylamine (APTES) to investigate the efficiency of modified activated carbon for CO2 adsorption. The modification parameters, such as the APTES concentration (2-5 wt%) and type of solvent (water and ethanol) were also investigated. Then, the modified activated carbon was characterized by nitrogen adsorption-desorption, scanning electron microscopy and Fourier transform infrared spectroscopy. The maximum CO2 adsorption capacity was 7602 mg/g for APTES-AC with 5 wt % APTES using ethanol as solvent. This study shows that the rice husk activated carbon modified with APTES could enhance the CO2 adsorption performance due to the physisorption and chemisorption.